Information System Integration in Citrus Packing Stations: A Key Driver for Product Quality and Customer Satisfaction - BENTALEB , Fatima Zahra; TAKI , Mounaim (Revue Internationale des Sciences de Gestion, 2023)
In the context of Morocco’s growing citrus exports and its involvement in the dynamic global market, Citrus Packing Stations play a crucial role as intermediaries in the distribution of processed agricultural commodities. The main aim of this study is to investigate the impact of integrating information systems on the improvement of product quality and customer satisfaction within the framework of CPS. Employing a mixed sequential exploratory approach, this research first draws on qualitative insights from five citrus packing case studies to generate survey items assessing the influence of information systems on product quality and customer satisfaction. In the subsequent quantitative phase, data from 40 CPS are analyzed using exploratory factor analysis and simple linear regression. Empirical findings demonstrate that the effective integration of information systems has a significant impact on enhancing product quality, improving customer satisfaction, and establishing a strong relationship between these two variables. The results underscore the broader importance of integrating information technologies into the context of supply chain management, hence providing prospects for further academic research in this field. The population size also suggests larger-scale investigations in order to expand the analytical framework.